2021
DOI: 10.1038/s41598-021-03841-4
|View full text |Cite
|
Sign up to set email alerts
|

Controlled rate slow freezing with lyoprotective agent to retain the integrity of lipid nanovesicles during lyophilization

Abstract: We designed a novel lyophilization method using controlled rate slow freezing (CSF) with lyoprotective agent (LPA) to achieve intact lipid nanovesicles after lyophilization. During the freezing step, LPA prevented water supercooling, and the freezing rate was controlled by CSF. Regulating the freezing rate by various liquid media was a crucial determinant of membrane disruption, and isopropanol (freezing rate of 0.933 °C/min) was the optimal medium for the CSF system. Lyophilized lipid nanovesicle using both C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In the present study, we found that the lyophilization procedure and lyoprotectant were related to each other rather than acting independent of each other [33][34][35] . The suitable lyoprotectant increased the eutectic point and collapsed the temperature of the system.…”
Section: Introductionmentioning
confidence: 51%
“…In the present study, we found that the lyophilization procedure and lyoprotectant were related to each other rather than acting independent of each other [33][34][35] . The suitable lyoprotectant increased the eutectic point and collapsed the temperature of the system.…”
Section: Introductionmentioning
confidence: 51%